Detection of canine distemper virus (CDV) neutralising antibodies in small ruminants during peste-des-petits-ruminants virus (PPRV) surveillance in Zambia - Lysholm, Sara; Logan, N.; Lindahl, Johanna F.; Berg, M.; Johansson, E.; Bergkvist, P.K.; Dautu, G.; Chazya, R.; Willett, B.J.; Munyeme, M.; Wensman, J.J. (BioMed Central, 2025)
Canine distemper virus (CDV) is endemic in Zambia, while peste-des-petits-ruminants virus (PPRV) has not been detected. This study screened 962 farmed goats and 237 small ruminants at informal markets for PPRV antibodies using c-ELISA. A subset (n = 29) was re-analysed with virus neutralisation assays (VNA) for antibodies to PPRV and CDV due to cross-reactivity concerns. c-ELISA indicated 6.44% PPRV seroprevalence on farms and 3.80% at markets. While VNA detected no PPRV antibodies, 45% (13/29) tested positive for CDV, possibly suggesting cross-reactivity. Given the study’s limitations, further research is needed to determine whether PPRV is present in Zambia and assess potential cross-reactivity.